ONTOGENIC VARIATION OF OXYGEN-UPTAKE IN THE PITVIPER BOTHROPS MOOJENI (SERPENTES, VIPERIDAE) - Cruzneto, A. P.; Abe, Augusto Shinya [UNESP] (Elsevier B.V., 1994)
The scaling of oxygen uptake was measured along the ontogeny, in the neotropical pitviper Bothrops moojeni. Allometric relationship between oxygen uptake and body mass, quantified for juveniles, sub-adults and adults, showed the same mass coefficient and exponent. The uniformity of mass constants along ontogeny suggests that B. moojeni is energetically homomorphic. Variation in mass seem to be the sole determinant of oxygen uptake, and structural modifications have no effect on the metabolic rate. Applications of the homomorphism principle to assess variations in mass coefficient and exponent for intraspecific analysis of metabolism in reptiles are discussed. B. moojeni had an oxygen consumption in the range reported for viperids, but lower than that for colubrid snakes of similar size. Possible causative reasons for this pattern is discussed.
Keywords: OXYGEN UPTAKE; BOTHROPS MOOJENI